Improvement Learning Outcomes of Sepaktakraw Basic Techniques Using Audiovisual Media During Covid-19 Pandemic in PJOK Students of Sriwijaya University - Al-Amien, M. Razif; Iyakrus, Iyakrus; Sumarni, Sri (Journal of Research and Educational Research Evaluation, 2021)
This study aims to produce audiovisual based learning media during Covid-19 Pandemic to improve the Sepaktakraw basic technique in Physical Education, Sport, Health and Recreation Students in Sriwijaya University with a total of 41 students by using a limited trial (small group) to 11 students and a vast trial (large group) by using 30 students. Analysing technique in this research is a linear regression model. The results in this study indicate that the implementation of audiovisual media based learning process with Sepaktakraw basic technique is used in Physical Education, Sport, Health and Recreation Students of Sriwijaya University. According to material experts of obtained a percentage of 88% (very good) and media experts of obtained of 84,61% (very good) category. The pre-test results was found to have average value of 64,67 and the post-test result was found to have average value of 90,80 with F count < 0,05, that means is a significant difference between student knowledge before and after watching the video of Sepaktakraw basic technique. It can be concluded that audiovisual based learning of media to improve Sepaktakraw game technique in Physical Education, Sport, Health and Recreation Students in Sriwijaya University are valid, practical and feasible to use.